From farm to table: assessing the status and health risk assessment of heavy metal pollution in rice in Henan Province - Yan, Yumeng; Mao, Zhenxing; Wang, Xinlu; Chen, Zhiwei; Ma, Cuicui; Wei, Dandan; Yan, Wenjing; Wu, Xueyan; Guo, Yao; Xu, Haoran; Han, Guozhen; Han, Erbao; et al. (Frontiers in Public Health, 2025)
IntroductionIn recent years, industrial and agricultural advancements in Henan Province have increased heavy metal contamination in rice, raising public concerns. The aim of this study was to investigate the contamination levels of five heavy metals, cadmium (Cd), chromium (Cr), lead (Pb), mercury (Hg), and inorganic arsenic (As), in rice from Henan Province and to assess potential health risks.MethodsA total of 6,632 rice samples were collected from 18 regions between 2020 and 2022. The samples were analyzed for Cd, Cr, Pb, Hg, and As using inductively coupled plasma mass spectrometry (ICP-MS). Detection rates were compared using the chi-square test, and health risks were assessed for the three populations (adults, children and toddlers) according to USEPA guidelines.ResultsThe results of the study showed that As had the highest detection rate of 99.59%, followed by Cd (27.69%), Cr (22.57%), Pb (2.25%) and Hg (1.95%). Cd levels were significantly higher in urban areas (30.42%) than rural areas (23.13%) (P < 0.001). The detection rate of Cd was higher in the southern region compared to other regions, while the detection rate of Cr in the eastern region was the highest among all regions. The health risk assessment showed that the Hazard Quotient (HQ) for inorganic As exceeded 1. However, children and toddlers were at relatively higher risk of exposure to As compared to adults.ConclusionThis study revealed the current status of heavy metal contamination in rice in Henan, particularly highlighting the presence of As as a significant health hazard for children and toddlers. Consequently, it is recommended that the relevant authorities should strengthen the monitoring and control of food safety in order to effectively protect public health.